Dynamics of Insulin Secretion from EndoC-βH1 β-Cell Pseudoislets in Response to Glucose and Other Nutrient and Nonnutrient Secretagogues - Hiroki Teraoku; Sigurd Lenzen (Journal of Diabetes Research)
The dynamics of insulin secretion were characterized in response to a variety of physiological and pharmacological stimulators and other compounds in perifused pseudoislets generated from cells of the EndoC-βH1 β-cell line. Perifusion of EndoC-βH1 pseudoislets with the physiological stimulus glucose (16.7 mM) induced sustained insulin secretion, which was inhibited by mannoheptulose. The adenylate cyclase activators IBMX and forskolin strongly potentiated this secretion. Glibenclamide, a Kir 6.2 potassium channel blocker, and Bay K 8644, an opener of the voltage-sensitive Ca2+ channel, also potentiated glucose-induced insulin secretion. The dynamics of insulin secretion from EndoC-βH1 pseudoislets were characterized by an insulin secretory response to glucose starting within 1-2 min and passing over without interruption into a sustained phase of insulin release for the whole stimulation period. This lack of a transient decline between the first and the second phases of insulin release is an indication for a quick supply of insulin secretory granules from the reserve pool to the docking sites below the plasma membrane. Thereby, new secretory granules are directly made available for sustained exocytosis of insulin in EndoC-βH1 β-cells. The study shows that EndoC-βH1 β-cell pseudoislets are well suited for kinetic analyses of insulin secretion.